2014
DOI: 10.2460/javma.244.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Associations between infectious bovine keratoconjunctivitis at weaning and ultrasongraphically measured body composition traits in yearling cattle

Abstract: Objective—To assess associations between infectious bovine keratoconjunctivitis (IBK) diagnosed at weaning and production traits in yearling beef calves. Design—Retrospective population-based cohort study. Animals—1,882 Angus calves. Procedures—Angus calves from 1 farm were evaluated over 7 years. The association between yearling body production traits and detection of IBK lesions at weaning was evaluated. Results—Yearlings that had evidence of IBK at weaning had less 12th rib fat depth, ribeye area, and body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 17 publications
1
16
1
Order By: Relevance
“…The ocular pain associated with IBK along with reduced vision and subsequent reduced feed intake most likely account for reduced weight gains in cattle with IBK. 2,[30][31][32] In the most severe cases, corneal rupture can occur resulting in permanent blindness (see Fig. 10).…”
Section: Patient Evaluation Overviewmentioning
confidence: 99%
“…The ocular pain associated with IBK along with reduced vision and subsequent reduced feed intake most likely account for reduced weight gains in cattle with IBK. 2,[30][31][32] In the most severe cases, corneal rupture can occur resulting in permanent blindness (see Fig. 10).…”
Section: Patient Evaluation Overviewmentioning
confidence: 99%
“…Other explanatory variables included in each model as potential effect modifiers or confounders of the association between IBK and weight at ultrasonographic evaluation were birth weight, season, sex of calves after weaning (bull, heifer, or steer), ADG (weaning to yearling weight), preweaning management group, postweaning management group, year of calving, season of calving, the interaction between year and season, and age at ultrasonographic evaluation37 …”
Section: (A) Clearly Define All Outcomes Exposures Predictors Potmentioning
confidence: 99%
“…The rationale for use of these parameters was that results of a prior study suggested that calves with IBK weighed approximately 7.5 kg less at weaning than unaffected calves, and the prevalence of IBK was approximately 33% in the study herd.37 …”
Section: (C) If a Formal Sample‐size Calculation Was Used Describementioning
confidence: 99%
“…Economic impacts due to M. bovis-induced Pink Eye may be significant, particularly with regards to loss of milk production, and also significant weight reduction and loss of condition in affected animals [3]. To date, the bacterium is relatively poorly studied and in particular, little is known regarding the cell surface carbohydrate structures that are possible virulence factors for this microorganism.…”
Section: Introductionmentioning
confidence: 99%